Hemophagocytic Lymphohistiocytosis after ChAdOx1 nCoV-19 Coronavirus Vaccination in a Patient with no Known Comorbidities - Nitin Rai; Saumitra Misra; Shashank Prajapati; Shubhajeet Roy; Geeta Yadav (Indian Journal of Medical Specialities)
Hemophagocytic lymphohistiocytosis (HLH) is an inflammatory condition where there is marked cytopenia and large-scale activation of macrophages and CD8+ cytotoxic T cells. HLH may be of two types – primary HLH caused by genetic abnormalities and secondary HLH due to infections, malignancies, autoimmune disorders, rheumatologic disorders, and metabolic dysfunctions. We describe a case of HLH following the first dose of the ChAdOx1 nCoV-19 Corona Virus vaccine. In this patient, there was no clear precipitant of HLH. The most probable explanation could be intense immune activation by vaccine constituents producing aberrant activation of inflammatory cytokines. There were no signs of infection or malignancy. Since our patient was clinically stable, his symptoms had resolved and HLH parameters had improved, no HLH-specific therapy was given.